Profiles of design-based learning experiences among undergraduate engineering students in an application-oriented Chinese university - Fang Chen; Gede Rasben Dantes; Kadek Rihendra Dantes; Dessy Seri Wahyuni (International Journal of Evaluation and Research in Education (IJERE), 2026)
Design-based learning (DBL) is widely promoted in engineering education, yet there is limited evidence on how students experience DBL when a common framework is implemented across multiple programs. This study examined support for four DBL phases—problem exploration (PE), design generation (DG), prototype iteration (PI), and reflection and evaluation (RE)—in undergraduate engineering programs at an application-oriented university in China. A 12-item DBL phases scale was developed from this framework and prior work in design-oriented engineering education and was completed by 407 students who had taken at least one DBL-based course in 12 programs. Partial least squares confirmatory factor analysis supported a four-factor structure with satisfactory reliability and convergent validity. To capture heterogeneity that is often obscured by average scores, a person-centered profiling approach was adopted. K-means cluster analysis of the four phase scores yielded three DBL experience profiles—high, moderate, and low intensity—that differed mainly in level rather than in shape across phases and were distributed across all programs and year levels. Grounded in engineering design and experiential learning perspectives, the phase-based scale and profiles offer a pragmatic tool for monitoring DBL implementation and for targeting professional development where students most often report low-intensity DBL.